Preliminary characterization and ecotoxicity assessment of paperboard industry waste (Revista de Ciências Agroveterinárias, 2020)
Paper and paperboard industry generate solid waste that demands correct treatment or disposal. The objective of this work was to characterize the solid waste of two paperboard industries located in Santa Catarina and to assess its ecotoxicity. The characterization involved the determination of moisture, ashes, and cellulose content. Ecotoxicity tests included avoidance behavior tests with earthworms (Eisenia andrei), reproduction tests with collembolans (Folsomia candida), and a test of germination and growth of roots of lettuce (Lactuca sativa). Results of the ecotoxicity tests were assessed using ANOVA followed by tests of Tukey and Dunnett and Fisher exact test (p
Keywords: ecotoxicological testes; cardboard industry; ETE sludge